THERMOKARST DYNAMICS IN WESTERN SIBERIA: INSIGHTS FROM DENDROCHRONOLOGICAL RESEARCH - Agafonov L.; Strunk H.; Nuber T. (My University, 2004)
Thermokarst dynamics and their underlying causes are investigated and reconstructed on the basis of Muzhy weather station records (Western Siberia) of air temperature, precipitation and snow cover, and a tree-ring chronology analysis of Siberian stone pine (Pinus sibirica Du Tour). The results indicate that the development of thermokarst over the last 50 years has depended primarily on increasing precipitation rather than increasing air temperature. Reconstruction of past thermokarst borderlines shows that the rate of thermokarst expansion in the second half of the 20th century increased to 7.4 cm/year, as compared to past rates ranging from 4 to 8.1 cm/year.
Keywords: Thermokarst; Precipitation; Air temperature; Tree-ring chronologies; Reconstruction